Direct Effects of Esmolol and Landiolol on Cardiac Function, Coronary Vasoactivity, and Ventricular Electrophysiology in Guinea-Pig Hearts - Shigehiro Shibata; Yosuke Okamoto; Shigeatsu Endo; Kyoichi Ono (Elsevier, 2012)
The ultra-short acting, selective β1-adrenergic antagonists landiolol and esmolol are widely used perioperatively; however, little is known about their acute direct actions on the heart. The current study utilized the Langendorff perfused heart system to measure changes in cardiac function and hemodynamics in response to each drug. Furthermore, electrophysiological analysis was performed on isolated ventricular myocytes. Direct application of esmolol significantly decreased systolic left ventricular pressure and heart rate at concentrations > 10 μM, while it dose-dependently increased coronary perfusion pressure. Esmolol also shortened the action potential duration (APD) in a concentration-dependent manner, an action maintained even when the delayed rectifier K+ current or ATP sensitive K+ current was blocked. Moreover, esmolol inhibited both the inward rectifier K+ current (IK1) and the L-type Ca2+ current (ICaL) and increased the outward current dose-dependently. In contrast, landiolol had minimal cardiac effects. In the Kyoto Model computer simulation, inhibition of either IK1 or ICaL alone failed to shorten the APD; however, an additional increase in the time-independent outward current caused shortening of the APD, equal to that induced by esmolol. In conclusion, esmolol directly inhibits cardiac performance significantly more so than landiolol, an effect revealed to be at least in part mediated by esmolol-induced APD shortening. Keywords:: esmolol, landiolol, Langendorff perfusion, patch clamp, coronary perfusion pressure